Women Entrapped by the Past: The House in Paris and A World of Love by Elizabeth Bowen - Lytovka, Olena (Leitura Flutuante, 2013)
The uncanny atmosphere in E. Bowen’s novels and short stories is often related to the house and felt by its female inhabitants. Lilia in A World of Love, Karen in The House in Paris and other female characters experience the presence of something disturbing and frightening in the house, perceive the domestic space as strange, sinister and feel entrapped there.Relying on psychoanalytic literary criticism and G. Bachelard’s theory of space, I will argue that the uncanniness of the house originates in the women’s traumatic experience of the past. The haunted house appears to be a manifestation of “the crisis of the proper” dissolving the certainty about herself and the world. The house traditionally being associated with woman’s domain, symbolically representing the female body become the embodiment of her inner world with its uneasiness, anxieties and fears.